DIFFERENTIAL RESPONSE TO STRUCTURE OF ADVANCE ORGANIZERS IN SCIENCE INSTRUCTION. - Koran Jr., John J.; Koran, Mary Lou (Journal of Research in Science Teaching, 1973)
The article focuses on the experiment which was designed to investigate differences in learning from written materials preceded by advance organizers. The subjects were randomly assigned to treatment conditions wherein programmed material on insects was preceded by introductory passages containing: (1) higher level generalizations and specific examples; (2) higher level generalizations without examples; or (3) a control passage. Furthermore, random assignment determine the membership in treatment groups and that criterion performance were immediate and delayed post test performance and errors during instruction. Results of the analysis of variance of the treatment effects indicated that the three treatments were about equally effective in terms of promoting retention and program errors.